A systematic literature review to identify ethical, legal, and social responsibilities of nonprofit organizations when funding clinical trials in pediatric cancer. Issue 9 (27th June 2022) - Rahimzadeh, Vasiliki; Wolfert, Susan; Buenger, Vickie; Campbell, Cindy; French, Robin; Ludwinski, Donna; Weinstein, Amy; Barrett, Caitlyn
Abstract: Nonprofit organizations (NPOs) play critical roles as funding sources, research partners, and disseminators of drug developments in pediatric cancer. Yet the literature provides limited guidance about ethical best practices when NPOs make trial funding decisions in this space. We conducted a systematic review of the literature indexed in PubMed and Web of Science to identify the ethical, legal, and social responsibilities of NPOs to four key stakeholder groups in funding pediatric cancer trials: (i) patients/families, (ii) researchers, (iii) industry sponsors, and (iv) donors. We applied the lifecycle framework for patient engagement in drug research and development proposed by Geissler and colleagues to analyze themes related to NPOs' responsibilities across 54 articles that met our inclusion criteria. Emergent themes included transparency surrounding conflicts of interest, the rigor of scientific review, and communication with patients/communities about trial progress. Our research identified critical gaps in best practices for negotiating research partnerships, managing competing research priorities, and pursuing alternative financing models including venture philanthropy. Results from our review informed a set of best practices to guide NPOs in making trial funding decisions that align with stakeholder values and interests.